Fabrication of Electrospun Polyamide-6/Chitosan Nanofibrous Membrane toward Anionic Dyes Removal - Mozhdeh Ghani; Ali Akbar Gharehaghaji; Mokhtar Arami; Negar Takhtkuse; Babak Rezaei (Journal of Nanotechnology)
Nanofibrous filter media of polyamide-6/chitosan were fabricated by electrospinning onto a satin fabric substrate and characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and water contact angle (WCA). Anionic dye removal capability of the filter was investigated for Solophenyl Red 3BL and Polar Yellow GN, respectively, as acidic and direct dyes were investigated with respect to solution parameters (pH and initial dye concentration) and membrane parameters (electrospinning time and chitosan ratio) through filtration system. Experiments were designed using response surface methodology (RSM) based on five-level central composite design (CCD) with four parameters to maximize removal efficiency of the filter media. Moreover, the effect of parameters and their likely interactions on dye removal were investigated by mathematically developed models. The optimum values for solution pH, initial dye concentration, electrospinning time, and chitosan ratio were predicted to be 5, 50 mg/L, 4 hr, 30% and 5, 100 mg/L, 4 hr, 10%, respectively, for achieving 96% and 95% removal of Solophenyl Red 3BL and Polar Yellow GN. Evaluation of the estimation capability of applied models revealed that the models have a good agreement with experimental values. This study demonstrated that polyamide-6/chitosan nanofibrous membrane has an enormous applicable potential in dye removal from aqueous solutions.